Identification of Differentially Expressed Genes and Key Pathways in the Dorsal Root Ganglion After Chronic Compression - Du, Zhanhui; Yin, Sen; Song, Xiuhui; Zhang, Lechi; Yue, Shouwei; Jia, Xiaofeng; Zhang, Yang (Frontiers in Molecular Neuroscience, 2020)
Neuropathic pain (NP) is caused by primary or secondary impairment of the peripheral or central nervous systems. Its etiology is complex and involves abnormal patterns of gene expression and pathway activation. Using bioinformatics analysis, we aimed to identify NP-associated changes in genes and pathways in L4 and L5 dorsal root ganglia (DRG) in a rat model of NP induced by chronic compression of the DRG (CCD). Genome-wide transcriptional analyses were used to elucidate the molecular mechanisms underlying NP. We screened differentially expressed genes (DEGs) 7 days after CCD in comparison with sham-operated controls. Quantitative real-time polymerase chain reaction (RT-qPCR) and western blotting were used to confirm the presence of key DEGs. Kyoto Encyclopedia of Genes and Genomes (KEGG)-pathway analysis of DEGs and global signal transduction network analysis of DEGs were also conducted. The CCD group developed clear mechanical and thermal allodynia in the ipsilateral hind paw compared with the sham group. This comparison identified 1887 DEGs, with 1156 upregulated and 731 downregulated DEGs, and 123 DEG-enriched pathways. We identified the key candidate genes that might play a role in the development of NP, namely phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit gamma (Pi3k), Janus kinase 2 (Jak2), jun proto-oncogene, AP-1 transcription factor subunit (Jun), and interleukin 6 (IL-6), and syndecan 1 (Sdc1) by analyzing the global signal transduction network. RT-qPCR and western blot analysis confirmed the microarray results. The DEGs Pi3k, Jak2, Jun, IL-6, and Sdc1, and the cytokine signaling pathway, the neuroactive ligand-receptor interaction, the toll-like receptor signaling pathway, and the PI3K-Akt signaling pathway may have decisive modulatory roles in both nerve regeneration and NP. These results provide deeper insight into the mechanism underlying NP and promising therapeutic targets for its treatment.